Pengaruh Profitabilitas, Leverage, Size, dan Intensitas Modal Terhadap Penghindaran Pajak: (Studi Kasus Pada Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2023) - Vamian, Enggar; Winarko , Sigit Puji; Puspita , Erna (Business and Investment Review, 2025)
Tax avoidance is a method implemented by taxpayers safely and legally because the method used to avoid taxes is in accordance with applicable tax provisions and the methods or efforts made tend to exploit loopholes (grey areas) contained in tax laws and regulations that can be used to minimize the amount of tax owed (Aini & Kartika, 2020). Several factors can influence the occurrence of tax avoidance, including profitability, leverage, size, and capital intensity. This study aims to examine the influence of Profitability, Leverage, size and capital intensity as factors that can cause tax avoidance either partially or simultaneously in the mining sector listed on the Indonesia Stock Exchange for the period 2019 - 2023. This study was conducted through a quantitative approach using secondary data, with a purposive sampling method to determine the sample studied. From 116 companies that became the population in this study, 180 annual financial reports were obtained from 36 companies that met the sample criteria. Data analysis techniques were in the form of descriptive statistics, classical assumption tests, Multiple Linear Regression Analysis, determinant coefficients and hypothesis testing using IBM SPSS Statistics software. The conclusion of this study is that (1) profitability, leverage, and size partially have a significant influence on tax avoidance. (2) capital intensity partially does not have a significant influence on tax avoidance. (3) profitability, leverage, size, and capital intensity simultaneously have a significant influence on tax avoidance.